2019
DOI: 10.1002/berj.3516
|View full text |Cite
|
Sign up to set email alerts
|

Special education teachers’ experienced burnout and perceived fit with the professional community: A 5‐year follow‐up study

Abstract: In many countries, including in Finland, promoting inclusive school practices supporting pupils’ equal rights for learning is the focus of school development. Special education teachers play a central intermediary role in developing inclusive school and classroom practices by providing support both for pupils and peer teachers. This may increase their risk of experiencing exhaustion, cynicism towards the teacher community and/or inadequacy in pupil–teacher relationships. However, the resources of a school's so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 69 publications
(114 reference statements)
1
6
0
1
Order By: Relevance
“…Previous studies reported that good working conditions, school structure, and professional interactions significantly improve the work climate and lead to further satisfaction among the teachers ( Lavian, 2012 ; Garwood et al, 2018 ). In contrast, unsupportive administration and lack of recognition were considered prime factors contributing to burnout among the special education teachers ( Perrone et al, 2019 ; Soini et al, 2019 ). Hence, this discussion implies that work climate can significantly predict burnout among teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies reported that good working conditions, school structure, and professional interactions significantly improve the work climate and lead to further satisfaction among the teachers ( Lavian, 2012 ; Garwood et al, 2018 ). In contrast, unsupportive administration and lack of recognition were considered prime factors contributing to burnout among the special education teachers ( Perrone et al, 2019 ; Soini et al, 2019 ). Hence, this discussion implies that work climate can significantly predict burnout among teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By increasing our understanding of the practises and perceptions of itinerant teachers who work in three main types of workplaces, not only will be able to accumulate practical knowledge in the field for better quality support but also help build a healthy working condition for itinerant teachers around the globe. This is important as global shortage of qualified teachers in the field is apparent and difficult working conditions are known to cause burnout, especially in special education (Kirchner & Diament, 1999; Mason-Williams et al, 2020; Soini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Huang (2014) suggested that occupational well-being is the quality of a worker’s experience and effectiveness at work. However, special education teachers experience less well-being in their work ( Ouellette et al, 2019 ; Soini et al, 2019 ). Children with special needs are individually diverse and require a high level of competence from special education teachers, yet their development is extremely slow.…”
Section: Occupational Well-beingmentioning
confidence: 99%